Endocrinopathies in paediatric-onset neuromyelitis optica spectrum disorder with aquaporin 4 (AQP4) antibody. (April 2018) - Hacohen, Yael; Messina, Silvia; Gan, Hoong-Wei; Wright, Sukhvir; Chandratre, Saleel; Leite, Maria Isabel; Fallon, Penny; Vincent, Angela; Ciccarelli, Olga; Wassmer, Evangeline; Lim, Ming; Palace, Jacqueline; et al.
The involvement of the diencephalic regions in neuromyelitis optica spectrum disorder (NMOSD) may lead to endocrinopathies. In this study, we identified the following endocrinopathies in 60% (15/25) of young people with paediatric-onset aquaporin 4-Antibody (AQP4-Ab) NMOSD: morbid obesity ( n  = 8), hyperinsulinaemia ( n  = 5), hyperandrogenism ( n  = 5), amenorrhoea ( n  = 5), hyponatraemia ( n  = 4), short stature ( n  = 3) and central hypothyroidism ( n  = 2) irrespective of hypothalamic lesions. Morbid obesity was seen in 88% (7/8) of children of Caribbean origin. As endocrinopathies were prevalent in the majority of paediatric-onset AQP4-Ab NMOSD, endocrine surveillance and in particular early aggressive weight management is required for patients with AQP4-Ab NMOSD.